ASSA14-03-13 Superoxide-lowering Therapy with Tempol Improves Balance of Renal RAS Components in Obese Zucker Rats. (1st December 2014) - Luo, H; Wang, X; Chen, C; Wang, J; Zou, X; Li, C; Lu, X; Jiang, X; Yang, X; Jose, PA; Zeng, C
Abstract : Objective: Oxidative stress plays an important role in the pathogenesis of hypertension, particularly associated with obesity-related hypertension. Increased oxidative stress leads to an imbalance of the natriuretic and antinatriuretic factors of the renal renin angiotensin system (RAS). We hypothesise that superoxide-lowering therapy using tempol reverses this imbalance resulting to natriuresis and diuresis, thus lowering the blood pressure of obese Zucker rats. Methods: Lean and obese Zucker rats received regular or antioxidant enzyme superoxide dismutase (SOD) mimetic tempol (1.0 mmol/l) in the drinking water for 4 weeks. Results: Results showed that, compared with lean rats, obese rats exhibited higher blood pressures, higher levels of renal oxidative stress, accompanied by increased natriuretic responses to AT1 R antagonist (candesartan) and AT2 R agonist (CGP-42112A) and reduced natriuretic response to MasR agonist (ang-[1–7]). Moreover, obese rats had higher levels of ACE, AT1 R and AT2 R, lower levels of ACE2 and Mas receptors in the kidney. All of the above-mentioned abnormalities were reversed to some degree by tempol treatment. Conclusion: Our study indicates that superoxide-lowering therapy with tempol reverses the imbalance of renal RAS components in obesity-related hypertension, which would be helpful to restore the renal function and lower blood pressure.